Teaching and Curriculum in Understanding of Classics of Pedagogy - Bojan Mirić; Mirsada Zukorlić (Društvene i Humanističke Studije, 2022)
This paper presents the results of theoretical and historical research and study of ideas and thoughts of the classics of pedagogy from the XVII to the XIX century (J.A. Comenius, Jean J. Rousseau, H. Pestalozzi, J. Locke, and Johan F. Herbart). The subject of our study is a review of scientific ideas of pedagogical classics on teaching and curriculum. We see the significance of this paper in presenting the understanding of pedagogical classics on teaching and curriculum, many of which are still relevant and important today. Throughout history, teaching has grown from individual to frontal through a series of transitional forms, and its most modern form assimilates the positive achievements of previous development. When it comes to the curriculum, from the point of view of interpreting pedagogical historiography, there are curricula and programs (contents) that were studied in schools in that period. That is why we are guided by the idea that we look at modern pedagogical topics such as teaching and curriculum, from a historical aspect in the light of theories and ideas of the classics of pedagogy.